The effect of kangaroo mother care applied to the healthy newborns in the early postpartum period on breastfeeding: a randomized controlled trial - Sevda Korkut Oksuz; Sevil Inal (Journal of the Pakistan Medical Association, 2021)
Objective: This study aims to determine the effect of kangaroo mother care applied to the healthy newborns in the early postpartum period on breastfeeding. Methods: Our research was conducted over the period June 1 - August 25, 2016 at the obstetrics and maternity units in Istanbul. A of 112 healthy newborns and their mothers (56 in the study group and 56 in the control group) were recruited into a randomized controlled experimental study. The newborns in the study group were administered kangaroo mother care for 3 hours after birth while the control group of newborns was cared for using the unit’s standard postpartum procedures. The time the newborns in the study and control groups first started to breastfeed, the number of breastfeeding within the first 24 hours, the duration of their breastfeeding and suckling skills were evaluated. Results: It was found that newborns subjected to kangaroo mother care provided immediately after delivery started suckling at the breast sooner (P = .001), for a longer period (P = .001) and more frequently (P = .001) than the newborns provided with standard post-delivery care. While there was no difference between the groups in terms of initial suckling skills (P = .862), the newborns in the kangaroo mother care group were better at suckling in the 24th hour (P = .001). Continuous...